2005
DOI: 10.1128/iai.73.7.3937-3944.2005
|View full text |Cite
|
Sign up to set email alerts
|

Survival ofSalmonella entericaSerovar Typhimurium within Late Endosomal-Lysosomal Compartments of B Lymphocytes Is Associated with the Inability To Use the Vacuolar Alternative Major Histocompatibility Complex Class I Antigen-Processing Pathway

Abstract: Gamma interferon (IFN-␥)-activated macrophages use an alternative processing mechanism to present Salmonella antigens to CD8؉ T lymphocytes. This pathway involves processing of antigen in a vacuolar compartment followed by secretion and loading of antigenic peptides to major histocompatibility complex class I (MHC-I) molecules on macrophage cell surface and bystander cells. In this study, we have shown that B lymphocytes are not able to process Salmonella antigens using this alternative pathway. This is due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 67 publications
1
31
1
2
Order By: Relevance
“…BALB/c mice were intraperitoneally infected with fifty bacteria, either Salmonella WT-GFP or Salmonella Δ sopB- GFP, as established in our previous work [42,43]. Eighteen hours post-infection, we evaluated Akt activation and YAP phosphorylation in splenic B cells using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…BALB/c mice were intraperitoneally infected with fifty bacteria, either Salmonella WT-GFP or Salmonella Δ sopB- GFP, as established in our previous work [42,43]. Eighteen hours post-infection, we evaluated Akt activation and YAP phosphorylation in splenic B cells using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the downregulation of NLRC4 in B cells may also have an impact on Salmonella replication and phagosomal maturation. Indeed, we have observed that Salmonella resides in a lysosomal compartment, and large numbers of bacteria are recovered from this compartment (8).…”
Section: Discussionmentioning
confidence: 96%
“…In fact, Salmonella survives more efficiently within B cells than in macrophages, and it can be recovered from splenic B cells, bone marrow B cell precursors, and plasma cells after a single-dose inoculation (8). However, the mechanisms used by Salmonella to survive within B cells are not established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations